PSYCHOLOGICAL POSSIBILITIES OF DEVELOPMENT OF CREATIVE-PRACTICAL SKILLS OF FUTURE PRIMARY CLASS TEACHERS - J. B. Mamadiyorov (International Scientific and Current Research Conferences, 2023)
This article presents the psychological possibilities of developing the skills of creative and practical activity of students of the direction "primary education and sports and educational work " of higher educational institutions.